The relationship between dynamic price and dynamic unemployment: the case of the Central European-3 and the Baltic Tigers - Dumlao, Luis F (Archīum Ateneo, 2014)
Convention specifies the relationship between price and unemployment in terms of the Phillips curve (PC) where inflation and the rate of unemployment are correlated. This paper uses a variant of the PC that is more consistent with the relationship between price and output as depicted in the aggregate supply (AS) curve. The relationship between price and unemployment using convention and its variant is tested on Poland, the Czech Republic, Hungary, Estonia, Latvia, Lithuania and the pooled data. The Expectations Augmented (EA) is able to track a negative relation between inflation and unemployment better than the New Keynesian (NK) is able. Within the EA runs, the convention is able to track the same negative relation better than the variant, but one has to be cautious given the implied results.